Strategi Meningkatkan Literasi Masyarakat atas Program Penjaminan Simpanan oleh LPS - Aep Saefullah; Elvira Sitna Hajar (LITERATUS, 2022)
The purpose of this research is to identify strategies and steps for increasing public awareness of the Deposit Insurance Corporation program. The qualitative approach was used in this study. The Simple Random Sampling technique was used in this study, which had 150 respondents. Data was gathered using observation, visual analysis, literature review, and interviews. According to the study's findings: 1. Many people are still unaware of and misunderstand the Deposit Insurance Corporation's programs, duties, functions, and authorities (LPS). 2. The public can learn more about the Deposit Insurance Corporation (LPS) guarantee programs by visiting the website and social media, or by visiting the nearest bank. Inquire directly with the LPS office or regional representative about clarification of information. Furthermore, through the socialization of activities both in person and online, 3. Public literacy steps and strategies for the IDIC guarantee program include: a) intensive program socialization to the community, both offline and online, in the form of seminars, workshops, webinars, and so on. b) The significance of involving members of the community (universities, Ormas, NGOs), as well as stakeholders from banking and non-financial financial institutions. (c) LPS takes the ball and walks straight to the center of the community gathering point to introduce the institution. d) Social media optimization for LPS across multiple platforms. e) Increase public trust by outperforming LPS performance standards. f) Creating user-friendly digital applications for the general public. g) Creating poster flyers to be distributed at the offices of banking and non-banking financial institutions